Prom1 Function in Development, Intestinal Inflammation, and Intestinal Tumorigenesis - Karim, Baktiar O.; Rhee, Ki-Jong; Liu, Guosheng; Yun, Kyuson; Brant, Steven R. (Frontiers in Oncology, 2014)
Prom1/CD133 has been identified in colorectal, hepatocellular, and pancreatic cancer as a cancer stem cell marker and has been used as such to predict colon cancer recurrence in humans. Its potential molecular function as well as its role as a marker of intestinal regeneration is still not fully known. We evaluated the role of Prom1 in intestinal regeneration in inflammatory bowel disease, determined the function of Prom1, and characterized the effect of a lack of Prom1 on intestinal tumor formation in animal models. Our results suggest that Apc mutations lead to an increase in Prom1 expressing cells in the intestinal crypt stem cell compartment and in early intestinal adenomas. Also, Prom1 knockout mice are more susceptible to intestinal tumor formation. We conclude that Prom1 likely plays a role in regulating intestinal homeostasis and that these results clearly illustrate the role of Prom1 in intestinal regeneration. We further conclude that Prom1 may provide a novel therapeutic target for patients with gastrointestinal conditions such as inflammatory bowel disease, short bowel syndrome, and colorectal cancer.